2020
DOI: 10.1177/0363546520934786
|View full text |Cite
|
Sign up to set email alerts
|

Repair Integrity and Retear Pattern After Arthroscopic Medial Knot-Tying After Suture-Bridge Lateral Row Rotator Cuff Repair

Abstract: Background: Type 2 failure is a big issue after suture-bridge rotator cuff repair, which may be because of stress concentration at the medial row stitches. We have been performing medial knot-tying after suture-bridge lateral row repair to avoid the stress concentration. This study aimed to evaluate clinical and radiological outcomes after arthroscopic rotator cuff repair using this technique. Hypothesis: This technique would yield better radiological outcomes with a reduced type 2 failure rate compared with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…For this reason, the application of a meticulous technique to reduce the type 2 failure rate plays an important role. In a recent study, Takeuchi et al 30 introduced a new knot-tying SB RCR technique: "arthroscopic medial knot-tying after suture-bridge lateral row rotator cuff repair." In this technique, medial knots were tied after the insertion of lateral-row anchors and formation of the SB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the application of a meticulous technique to reduce the type 2 failure rate plays an important role. In a recent study, Takeuchi et al 30 introduced a new knot-tying SB RCR technique: "arthroscopic medial knot-tying after suture-bridge lateral row rotator cuff repair." In this technique, medial knots were tied after the insertion of lateral-row anchors and formation of the SB.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]31 Type 2 (medial) retears can cause impingement and are associated with pain and lower shoulder function and quality of life. 19,30 Moreover, revision of type 2 failure is more challenging. 1 Therefore, an SB RCR technique that uses knotless medial-row anchors has been developed to avoid overtensioning of the suture-tendon junction at the medial row and improve vascular inflow.…”
mentioning
confidence: 99%
“…Rotator cuff tendons were repaired using the medial knot-tying after suture-bridge lateral-row repair techniques. 13 , 25 , 27 One to 3 triple-loaded suture anchors were inserted at the medial border of the footprint in accordance with tear size, and two different sutures were passed through the rotator cuff at a time. Suture-bridge lateral-row fixation was initially performed using 2 of 3 sutures from an anchor.…”
Section: Methodsmentioning
confidence: 99%
“…In 2010, Hotta et al proposed that the medial row knot of the suture bridge could increase subacromial impact and produce aseptic inflammation, causing persistent shoulder pain in patients after operation 9 . Likewise, Takeuchi et al revealed that the reason may be that the medial row suture and knots will lead to stress concentration and cutting hanging at the tendon-ventral junction, while the medial row knot increases the operation time and operation complexity, especially for novice arthroscopic doctors 5 . Besides, Kim et al recently proposed another reason for the failure of suture bridge may be that the closed cross structure of suture bridge blocks the blood supply of tendons from the medial abdomen to the tear area, resulting in difficulty in tendon-to-bone healing 10 .…”
Section: Introductionmentioning
confidence: 99%